A pilot study on the provision of tracheostomy healthcare and patient engagement in quality improvement measures: a global perspective. Issue 12 (24th January 2019) - Swords, C; Manji, A; Ward, E; Arora, A
Abstract: Background: Work describing patient and family outcomes after tracheostomy has indicated that patients do not feel prepared at the time of discharge. Objectives: To assess healthcare professional–patient interactions in tracheostomy care and the current provision of care. Method: A global electronic survey was disseminated via e-mail. Results: The majority of respondents were nursing or speech and language staff, from over 10 countries. Only 23 per cent of respondents' institutions routinely offered patients the ability to meet people with a tracheostomy pre-operatively. Only 31 per cent consistently provided or co-ordinated full nursing and equipment requirements on discharge. Only half of the institutions participated in tracheostomy quality improvement initiatives; less than one-third of these involved patients. Conclusion: The provision of tracheostomy care in hospital and at discharge can be improved. The current practice of clinician-led audit is becoming less viable; future initiatives should focus upon patient-centred outcomes to ensure excellence in healthcare delivery.